The use of benchmark for the improvement of the tobacco process - Cardoso, Josimara Santos; Moraes, Jorge André Ribas; Silva, André Luiz Emmel (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The current paper brings a study and how can be possible to improve the waste Tabaco process through the mass balance and the use of benchmarking. The research took place in an international company located in the state of Rio Grande do Sul and compared with other two companies located in different areas. The paper consists in two parts; one of them is to analyze the process, take information from the production and to construct the mass balance into the 3 companies. The second step consists in a creation of an action plan and involvement of the coordinates and responsible for the process where was possible to identify the opportunities for improvement and control of waste. At the end was identified the quantity of waste product and improve the production process.